What Shapes Colombias Foreign Position on Climate Change? - María Camila Bustos (Universidad de Los Andes, 2018)
Colombia presents a revealing and much needed case study which helps us to understand the formulation of foreign policy on climate change in rising developing countries. This paper analyzes the main factors which shape Colombias position, and provides useful insights into the evolution of the countrys international stance on climate change and the role in it of the bargaining among government agencies and interest groups. It concludes that Colombia´s policy has been governed by its institutional structure, ecological vulnerability, emission abatement costs, wish to enhance its global prestige and seek benefits from international cooperation, strategic aims at the United Nations climate negotiations, and the limited influence of domestic pressure groups.